Estimator's equipment installation man-hour manual - Page, John S. (Gulf Pub. Co., 1999)
This new edition is expanded to include 26 new man-hour tables on compressors, dryers, dampers, filters, coolers, and heaters. This manual eliminates guesswork and enables you to produce fast, accurate equipment installation labor estimates.
Chiefly tables.
: Production and composite rate. Boilers and heaters. Classification equipment. Compressors and air dryers. Conveyors and bucket elevators. Crystallizers. Dow therm units. Dry material blenders and feeders. Dryers and flakers. Dust collectors. Ejectors. Extractors. Fans and blowers. Filters. Flotation machines. Gas holders. Generators. Heat exchangers, evaporators, and condensers. Heating, ventilating, air-conditioning, and air-handling units. Hoist-overhead electric. Mixers and blenders. Pumps. Scales. Separators. Size reduction equipment. Thickeners. Vessels, reactors, and tanks. Waste treating equipment. Water treating equipment. Plate welding. Insulation and waterproofing. Supports. Pipe connections. Earthwork. Concrete. Scaffolding. Weight tables. Sample estimating form.
Keywords: Industrial equipment -- Installation -- Estimates -- Handbooks, manuals, etc.; elektronické knihy; electronic books